Intestinal Transplant Immunology and Intestinal Graft Rejection: From Basic Mechanisms to Potential Biomarkers - Rumbo, Martín (2023)
Intestinal transplantation (ITx) remains a lifesaving option for patients suffering from irreversible intestinal failure and complications from total parenteral nutrition. Since its inception, it became obvious that intestinal grafts are highly immunogenic, due to their high lymphoid load, the abundance in epithelial cells and constant exposure to external antigens and microbiota. This combination of factors and several redundant effector pathways makes ITx immunobiology unique. To this complex immunologic situation, which leads to the highest rate of rejection among solid organs (>40%), there is added the lack of reliable non-invasive biomarkers, which would allow for frequent, convenient and reliable rejection surveillance. Numerous assays, of which several were previously used in inflammatory bowel disease, have been tested after ITx, but none have shown sufficient sensibility and/or specificity to be used alone for diagnosing acute rejection. Herein, we review and integrate the mechanistic aspects of graft rejection with the current knowledge of ITx immunobiology and summarize the quest for a noninvasive biomarker of rejection.